Clinical Pharmacology, Clinical Efficacy, and Behavioral Toxicity of Alprazolam: A Review of the Literature - Verster, Joris C. (CNS Drug Rev, 2006)
Alprazolam is a benzodiazepine derivative that is currently used in the treatment of generalized anxiety, panic attacks with or without agoraphobia, and depression. Alprazolam has a fast onset of symptom relief (within the first week); it is unlikely to produce dependency or abuse. No tolerance to its therapeutic effect has been reported. At discontinuation of alprazolam treatment, withdrawal and rebound symptoms are common. Hence, alprazolam discontinuation must be tapered. An exhaustive review of the literature showed that alprazolam is significantly superior to placebo, and is at least equally effective in the relief of symptoms as tricyclic antidepressants (TCAs), such as imipramine. However, although alprazolam and imipramine are significantly more effective than placebo in the treatment of panic attacks, Selective Serotonin Reuptake Inhibitors (SSRIs) appear to be superior to either of the two drugs. Therefore, alprazolam is recommended as a second line treatment option, when SSRIs are not effective or well tolerated. In addition to its therapeutic effects, alprazolam produces adverse effects, such as drowsiness and sedation. Since alprazolam is widely used, many clinical studies investigated its cognitive and psychomotor effects. It is evident from these studies that alprazolam may impair performance in a variety of skills in healthy volunteers as well as in patients. Since the majority of alprazolam users are outpatients, this behavioral impairment limits the safe use of alprazolam in patients routinely engaged in potentially dangerous daily activities, such as driving a car.